THE IMPLEMENTATION OF SOCIAL RESPONSIBILITY ACTIVITY AT HOSPITAL: A CASE STUDY AT PUBLIC AND PRIVATE HOSPITALS IN MALANG - Amanda Chintia Putri Ammal (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to know and understand how the implementation of social responsibility activities in RSUD dr. Saiful Anwar as a public hospital and Lavalette Hospital as a private hospital in Malang. Besides the implementation of Social Responsibility at both hospitals, this research also aims to determine what are the differences between public hospital and private hospital in carrying out social responsibility activities. This research is classified as a qualitative study using descriptive approach. Case study is used to answer the problems in this study. Furthermore, to collect data, the study used interview, documentations and observation. The results of this study indicate that either public and private hospitals carry out social responsibility activities and fulfill the concept of triple bottom line, which are social aspect (people), environmental aspect (planet), and economy aspect (profit). In addition, the research also showed that there are some differences and similarities at both hospitals in carrying out social responsibility activities. First, although both hospitals do not have specific departments to handle social responsibility activities, the organization structure of RSUD dr. Saiful Anwar is more formal than Lavalette Hospital. Second, the cost incurred for social responsibility activities in RSUD dr. Saiful Anwar are structured and targeted on annual budgeting, while in Lavalette Hospital social responsibility budget is mostly unplanned or unbudgeted. Most of the social responsibility activities in Lavalette Hospital are based on orders from PT. Nusantara Sebelas Medika as the parent company. Thirdly, both hospitals have not made social responsibility reports separately. They are still reporting social responsibility spending on expense accounts in the annual financial report. Lastly, in its practice, social responsibility activities conducted by RSUD dr. Saiful Anwar is conducted implicitly, while in Lavalette Hospital is conducted explicitly.Key words: Social Responsibility, Triple Bottom Line Concept, Social Respomsibility Implementation, Budgeting, Reporting, Hospitals.